2020
DOI: 10.1016/j.ejrad.2020.109202
|View full text |Cite
|
Sign up to set email alerts
|

Role of computed tomography in predicting critical disease in patients with covid-19 pneumonia: A retrospective study using a semiautomatic quantitative method

Abstract: Background So far, only a few studies evaluated the correlation between CT features and clinical outcome in patients with COVID-19 pneumonia. Purpose To evaluate CT ability in differentiating critically ill patients requiring invasive ventilation from patients with less severe disease. Methods We retrospectively collected data from patients admitted to our institution for COVID-19 pneumonia between March 5th-24th. Patients were considered cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 27 publications
1
54
0
5
Order By: Relevance
“…Another semiquantitative study of 106 inpatients with COVID-19 pneumonia showed significant positive correlations between CT severity and levels of inflammatory cytokines such as interleukin-6 and interleukin-2R (27). Additional studies have observed similar correlations (22,28,29) CT severity scoring may show promise for clinical triage and assessment of prognosis, and higher CT severity scores predict clinical outcomes in COVID-19 (29,30). In a study of 572 hospitalized patients, 70% of patients with total lung involvement greater than 50% were admitted to the intensive care unit or died within seven days of a CT performed at admission, while these rates were lower for lung involvement of 26-50% (41%) and <25% (23%) (18).…”
Section: N P R E S Smentioning
confidence: 83%
See 2 more Smart Citations
“…Another semiquantitative study of 106 inpatients with COVID-19 pneumonia showed significant positive correlations between CT severity and levels of inflammatory cytokines such as interleukin-6 and interleukin-2R (27). Additional studies have observed similar correlations (22,28,29) CT severity scoring may show promise for clinical triage and assessment of prognosis, and higher CT severity scores predict clinical outcomes in COVID-19 (29,30). In a study of 572 hospitalized patients, 70% of patients with total lung involvement greater than 50% were admitted to the intensive care unit or died within seven days of a CT performed at admission, while these rates were lower for lung involvement of 26-50% (41%) and <25% (23%) (18).…”
Section: N P R E S Smentioning
confidence: 83%
“…Several studies have shown correlations between extent of parenchymal involvement at CT and clinical assessment of COVID-19 disease severity as defined by parameters such as severity of symptoms, oxygenation status, and certain laboratory measures of infection and inflammation. Semiquantitative and quantitative studies have shown significantly higher CT severity scores for patients with severe and critical disease than for those with less severe disease (17,(22)(23)(24)(25). For example, in one study of 189 inpatients, the average volume of lung involvement measured by semiautomated segmentation of parenchymal opacities on CT was higher in critically ill patients (38.5%) than in non-critically ill patients (5.8%), with a threshold of 23% distinguishing these two groups with 96% sensitivity and specificity (22).…”
Section: N P R E S Smentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the disease severity can be ascertained from the imaging findings, significantly supporting the clinicians in their clinical judgment and ensuring effective and timely management [ 7 ]. Prognosis can also be affected by the severity of the disease in the critically ill patients allowing appropriate selection of early involvement of the intensive care [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports suggest that the CXR [16] as well as chest CT [17] are able to predict whether the course of the disease will be moderate or severe in relation to the extent and morphology of pulmonary infiltrates on admission.…”
Section: Discussionmentioning
confidence: 99%